Centre-Local Relations in the Stalinist State, 1928-1941 - Rees, E. A. author. aut Link
XIV, 229 p.
Keywords: This book analyzes the development of the Stalinist state of the 1930s from the perspective of the changing nature of centre-local relations. It examines the trend toward greater central state control over the formation and implementation of economic policy and the shift towards increased state repression through a series of archive-based case studies of the centre's interactions with its republican and regional bodies. The book provides the basis for a new conceptualization of the Stalinist state.